Village Political Economy, Land Tenure Insecurity, and the Rural to Urban Migration Decision: Evidence from China - John T. Giles; Ren Mu (Institute for the Study of Labor (IZA), 2014)
This paper investigates the impact of land tenure insecurity on the migration decisions of China's rural residents. A simple model first frames the relationship among these variables and the probability that a reallocation of land will occur in the following year. After first demonstrating that a village leader's support for administrative land reallocation carries with it the risk of losing a future election, the paper exploits election-timing and village heterogeneity in lineage group composition and demographic change to identify the effect of land security. In response to an expected land reallocation in the following year, the probability that a rural resident migrates out of the county declines by 2.8 percentage points, which accounts for 17.5 percent of the annual share of village residents, aged 16 to 50, who worked as migrants during the period. This finding underscores the potential importance of secure property rights for facilitating labor market integration and the movement of labor out of agriculture.
Keywords: O12; O15; J61; Q15; R23; 330; migration; land tenure; property rights; China; village political economy